TINJAUAN PUSTAKA SISTEMATIS: PROGRAM EKTRAKURIKULER PRAMUKA UNTUK MELATIH KEMANDIRIAN SISWA SEKOLAH DASAR - Wahyuningrum, Fitri; Hidayat, Muhamad Taufik (UIN Sumatera Utara Medan, 2023)
This study aims to analyze the activities carried out during the scout extracurricular activities in elementary schools and the elements of independence contained in each activity. The method used in this writing issystematic literature review. The information used contains the character of independence. Processliterature review This is done by searching for relevant articles, evaluating by means of data extraction and then comparing the results of the literature. The database used isgoogle scholar. The results of this study indicate that (1) the weekly activities carried out during the Scout extracurricular take place can train students' self-reliance in stages and are well embedded, (2) the elements contained in each scouting activity form a pattern of student character well too. The implications of this research are: First, the teacher is able to provide training for instilling the character of independence for students through scout extracurricular activities. Second, parents can provide full support for their children to participate in various extracurricular activities. Third, students can get used to doing things independently, without bothering other people, so that students have a tough nature and don't depend on others. Furthermore, in this study the authors explain the various kinds of extracurricular activities that have been carried out in various elementary schools to train the independence of their students, and other elements that are instilled in each activity carried out.